Studies on the Use of Flagellin as an Immunostimulant and Vaccine Adjuvant in Fish Aquaculture - Wangkahart, Eakapol; Secombes, Christopher J.; Wang, Tiehui (Frontiers in Immunology, 2019)
Immunostimulants and vaccines are important for controlling infectious diseases in fish aquaculture. In this study we assess the potential of flagellin to be used for such purposes in rainbow trout (Oncorhynchus mykiss). A recombinant flagellin from the salmonid pathogen Yersinia ruckeri (YRF) has been produced previously by us and shown to be a potent activator of inflammatory cytokines, acute phase proteins and antimicrobial peptides in vitro. Here we show that YRF is the most potent inflammatory activator of three bacterial PAMPs (LPS, peptidoglycan and flagellin) tested. The host response to flagellin was next studied in vivo. The YRF modulated gene expression was examined in two systemic (spleen and liver) and two mucosa-associated (gills and skin) tissues. YRF injection initiated a transient systemic inflammatory response with key pro-inflammatory cytokines (IL-1β, TNFα, IL-6, and IL-11 etc.) and chemokines (CXCL_F4 and CXCL-8) induced rapidly (by 6 h) but subsiding quickly (by 24 h) in multiple tissues. Consequently, a variety of anti-microbial pathways were activated systemically with heightened expression of acute phase proteins, antimicrobial peptides and complement genes in multiple tissues, which was sustained to 24 h in the liver and mucosal tissues. The Th17 cytokine IL-17A/F1 was also induced in the spleen and liver, and Th2 cytokine IL-4/13 was induced in the liver. However, the anti-inflammatory IL-10 and the Th1 cytokine IFNγ were refractory. A secreted form of TLR5 (TLR5s) was induced by flagellin in all tissues examined whilst the membrane form was refractory, suggesting that TLR5s may function as a negative feedback regulator. Trout liver appeared to be an important organ responding to flagellin stimulation, with marked induction of IL-11, IL-23P19, IL-17C1, SAA and cathelicidin-2. YRF induced a strong antibody response. These antibodies reacted against the middle domain of YRF and were able to decrease YRF bioactivity. Intact YRF was necessary for its bioactivity, as deletion of the N-terminal, C terminal or middle domain of YRF led to functional loss. This study suggests that flagellin could be a potent immunostimulant and vaccine adjuvant for fish aquaculture.